Review on Documented Medicinal Plants used for the Treatment of Cancer - Joshi, Bhuwan C.; Juyal, Vijay; Sah, Archana N.; Verma, Piyush; Mukhija, Minky (Current Traditional Medicine, 2022)
Background: Cancer is a frightful disease and it is the second leading cause of death worldwide. Naturally derived compounds are gaining interest of research workers as they have less toxic side effects as compared to currently used treatments, such as chemotherapy. Plants are the pool of chemical compounds, which provide a promising future for research on cancer. Objective: This review paper provides updated information gathered on medicinal plants and isolated phytoconstituents used as anticancer agents and summarises the plant extracts and their isolated chemical constituents exhibiting anticancer potential on clinical trials. Methods: An extensive bibliographic investigation was carried out by analysing worldwide established scientific databases like SCOPUS, PUBMED, SCIELO, ScienceDirect, Springerlink, Web of Science, Wiley, SciFinder and Google Scholar etc. In the next few decades, herbal medicine may become a new epoch of medical system. Results: Many researches are going on medicinal plants for the treatment of cancer but it is a time to increase further experimental studies on plant extracts and their chemical constituents to find out their mechanism of action at molecular level. Conclusion: The article may help many researchers to start off further experimentation that might lead to the drugs for the cancer treatment.
Keywords: bioactive compounds